Are Patients With Schizophrenia Better Off With Lifetime Antipsychotic Medication?: Replication of a Naturalistic, Long-Term, Follow-Up Study of Antipsychotic Treatment. Issue 2 (March 2020) - Glick, Ira D.; Zamora, Daisy; Davis, John M.; Suryadevara, Uma; Goldenson, Andrea; Kamis, Danielle
Abstract: Purpose/Background: The question of whether people with schizophrenia should be treated with antipsychotics for life has been debated for decades. We recently reported results of 2 retrospective long-term naturalistic studies examining the association of medication adherence and global outcomes in different demographic samples. In both, we found that patients with a history of better adherence to antipsychotic medication had better quality of life outcomes. Using similar methodology, here we present such associations for a very different sample—patients with chronic schizophrenia with a long past history of antipsychotic treatment that had been treated for 19 to 53 years in a Veterans Affairs clinic. Methods: This is a retrospective, naturalistic, longitudinal 19- to 53-year (mean average, 33.5 years) lifetime follow-up of a consecutive series of patients with schizophrenia, who had at least 8 years of antipsychotic treatment. Lifetime data were collected on (1) their medication adherence, (2) long-term global outcome, and (3) life satisfaction. Outcomes were rated by 2 different clinicians, one with information on medication adherence (nonblind rater) and one without (blind rater). Linear regression models, adjusted for age, family support, substance use disorder, race, marital status, and number of years in treatment were used to estimate the association between adherence and each outcome. Results: A total of 20 patients were assessed. Medication adherence was positively associated with the blind clinician's rating of global outcome ( P = 0.049) and the Global Assessment of Functioning ( P = 0.021). In the nonblinded clinician's rating, medication adherence was positively related to global outcome ( P = 0.001) and to the patient's report of life satisfaction ( P = 0.028). Implications/Conclusions: This replication study, together with our previous 2 studies, is consistent with the recommendation for continuous, long-term treatment for chronic schizophrenia over many years of a patient's lifetime unless medically contraindicated.